Analisis Sistem Transivitas Wacana Politik dalam Media tempo.co tentang Berita Pilkada DKI Jakarta 2024 - Amir, Israwati; Nursalam; Mustafa, Irvan; Rahim, Abd; Shifa Salsabila; Syaidah (ALFABETA: Jurnal Bahasa, Sastra, dan Pembelajarannya, 2025)
The type of research for this article is qualitative research using a Systemic Functional Linguistics approach. The focus of this research is to describe the transitivity process of political discourse in the DKI Jakarta Regional Election news via tempo.co media. The data for this research are news texts obtained through the tempo.co media website. The data collection method for this research is using reading and note-taking techniques. The results of this research show that there are six types of transitivity processes found in the DKI Jakarta Pilkada news discourse via tempo.co media, namely, material processes, mental processes, verbal processes, behavioral processes, relational processes, and extensional processes. Material processes have clause structures, such as actor participants and goals, material processes, and circumstantial. Mental processes have a clause structure of sensory participants, phenomena, mental processes, and circumstantial problems. The verbal process has a clause structure, namely reporter, verbal process, and reported. The behavioral process has elements of behavioral participants, verbal behavioral processes, and phenomena. Relational processes have participant participants, relational processes attribute, and role circumstantial. Furthermore, the extensional process has elements of transitivity, namely existence, existential process, and circumstantial range